2011
DOI: 10.5194/aab-54-264-2011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex and terminal sire line on carcass characteristics of pork belly

Abstract: The objective of study was to evaluate the effect of sex and terminal sire line on pork belly composition of commercially produced pigs. The animals were progeny of White Meaty sows and three terminal sire lines: HA × PN, LA and YO × PN. Barrows: gilts ratio was 97:102. Pigs were slaughtered at average carcass weight 85.73-89.0 kg according to genotype. Day after slaughter, the dissection of right half sides was done. After that, the detailed dissection of trimmed belly to individual tissues (bones, meat, fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This represents a partial negation of the results obtained by the study of Bahelka et al (2011), who also proved the existence of quantitative differences between bellies from gilts and barrows. However, on the other hand our results almost fully confirms the study conducted by Vališ et al (2005), although the presented values of the variables were different.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This represents a partial negation of the results obtained by the study of Bahelka et al (2011), who also proved the existence of quantitative differences between bellies from gilts and barrows. However, on the other hand our results almost fully confirms the study conducted by Vališ et al (2005), although the presented values of the variables were different.…”
Section: Discussionmentioning
confidence: 51%
“…The lean meat content in belly has a significant economic impact on processing and consumer acceptance of pork (Bahelka et al, 2011); thus, it is advisable to determine this parameter precisely. The use in the equations of the lean meat content of the carcass is justified owing to its relationship, and this confirmed its relationship with the content of the meat in belly (Vališ et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In general terms, the weakest correlation was demonstrated in the abdominal plane, and the strongest in the dorsal plane. In caudal-cranial layout, the strongest correlations were noted in the third (Bahelka et al, 2011) plane, which was the opposite of the first plane. No distinctive qualitative parameters were observed that would correlate at a similar level for all locations, except for correlations L* and H* (from r = 0.36 to r = 0.84, all P ≤ 0.05).…”
Section: Resultsmentioning
confidence: 88%
“…Genotype/Breed Effect Various studies have shown that breed or genotype significantly affect some technological and sensory qualities of pork (Ellis et al 1999;Bahelka et al 2011;Bertol et al 2013). Ellis et al (1999) have shown that breed and genetic line largely affect pork eating quality, with the utilization of Duroc terminal sire lines as a common practice for improving this sensory quality.…”
Section: Pre-slaughter Factorsmentioning
confidence: 99%
“…Regardless of feed components, barrows usually have a higher fat deposition, which leads to higher backfat than gilts (Cromwell et al 1993;Fiego et al 2005;Benz et al 2010;Bahelka et al 2011) and the higher the fat deposition, the less the degree of unsaturation (Wood and Enser 1982), especially if de novo lipogenesis is not inhibited by dietary components. As such, barrows usually have lower PUFA, UFA:SFA, PUFA:SFA and higher SFA compared with gilts (Lonergan et al 1992;Benz et al 2010).…”
Section: Sex Effectsmentioning
confidence: 99%